(untitled) (Eurasian Journal of Ecology, 2018)
The study shows morphological features in the lung tissue of rats found after inhalation of dust of uranium ore. Destructive changes have been detected, both at the cellular and subcellular levels.The effect of radio-toxic factors at a dose of 50 MPC was accompanied by the development of acute focal serous inflammation in the wall of small bronchi and in the lung parenchyma in the early stages of the experiment, fibrosis of pneumonic foci and development of pronounced sclerotic changes in peribronchial tissue for 30 days. The increase in sclerotic changes in the bronchial wall was accompanied by the suppression of the reaction from the interstitial macrophages and bronchial associated lymphoid tissue, indicating that on the intense flow of compensatory processes. The electron microscopic studies confirmed the results obtained with light microscopy. Under the influence on animals with PUR at a dose of 50 MPC, destructive changes in the alveolar epithelium predominated from the early stages of the experiment. From 30 days up to 60 days marked development of severe fibrosis with a decrease in the respiratory surface. Compensatory reactions characterized by high degree of voltage in the form of regeneration A1, endothelial hypertrophy, high phagocytic activity of alveolar macrophages. Key words: dust of uranium ore, radio nuclides, lung disease.